The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1161/circulationaha.120.047000
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertrophic Memory After Regression of Exercise-Induced Physiological Myocardial Hypertrophy Is Mediated by the Long Noncoding RNA Mhrt779

Abstract: Background: Exercise can induce physiological myocardial hypertrophy (PMH), and former athletes can live 5-6 years longer than nonathletic controls, suggesting a benefit after regression of PMH. We previously reported that regression of pathological myocardial hypertrophy has antihypertrophic effects. Accordingly, we hypothesized that antihypertrophic memory exists even after PMH has regressed, increasing myocardial resistance to subsequent pathological hypertrophic stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…Oe-GDF11, sh-GDF11, and NC virus particles (1 × 10 11 viral genomes/ml) were administered by using a 300 μl syringe with 30 gauge needle to direct inject into the LV free wall (three evenly dispersed sites, 10 μl/site) in 8-week-old mice. Do not insert the syringe needle too deep to avoid piercing the ventricular wall muscles into the LV [ 30 ]. Twenty-four hours after IR or sham, the samples were harvested for total protein or mRNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Oe-GDF11, sh-GDF11, and NC virus particles (1 × 10 11 viral genomes/ml) were administered by using a 300 μl syringe with 30 gauge needle to direct inject into the LV free wall (three evenly dispersed sites, 10 μl/site) in 8-week-old mice. Do not insert the syringe needle too deep to avoid piercing the ventricular wall muscles into the LV [ 30 ]. Twenty-four hours after IR or sham, the samples were harvested for total protein or mRNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The destruction of intestinal barrier function and the change of GM composition may lead to abnormal production and absorption of microbial metabolites in patients with HF. Imbalance of intestinal microbial metabolites and intestinal epithelial dysfunction may lead to cardiac dysfunction, inflammation, malnutrition, and other diseases in patients with HF [57]. HF leads to changes in blood flow such as insufficient tissue perfusion and gastrointestinal congestion, which can change body's intestinal morphology, permeability, and abundance and composition Cardiovascular Therapeutics of GM, which in turn damages the intestinal barrier function, stimulates the inflammatory response, and accelerates its pathological development [58].…”
Section: Gm and Hfmentioning
confidence: 99%
“…A recent animal study found that moderate-intensity exercise training but not high-intensity interval training reduced cardiac fibrosis ( Table 1 ) and oxidative stress, improved cardiac function in aged (32-week-old) male mice ( Pei et al, 2021 ). Exercise hypertrophic preconditioning in mice could also alleviate cardiac fibrosis ( Table 1 ), hypertrophy and dysfunction at 1 week and 4 weeks post-TAC ( Lin et al, 2021 ). Therefore, moderate exercise can decrease cardiac fibrosis, but endurance exercise can induce cardiac fibrosis to some extent which may be related to the sex, age, and the exercise intensity.…”
Section: Exercise and Myocardial Fibrosismentioning
confidence: 99%